Characterization of a novel polymeric bioflocculant from marine actinobacterium Streptomyces sp. and its application in recovery of microalgae. (March 2020) - Sivasankar, Palaniappan; Poongodi, Subramaniam; Lobo, Anderson O.; Pugazhendhi, Arivalagan
Abstract: The present study has aimed to isolate and characterize a novel polymeric bioflocculant from the marine actinobacterium Streptomyces sp. and to evaluate its efficiency in the recovery of microalgae. Initially, the obtained polysaccharide based ABF was characterized for chemical composition. The yield, total sugar and protein contents of the bioflocculant were 4.94 g/L, 86.9% and 12.8%, respectively. The molar mass of the bioflocculant was estimated as 55 kDa. The monosaccharide composition of the bioflocculant was observed to be 72% of galactose, 22% of glucose, and 6% of mannose, respectively. The functional and structural characterizations of the bioflocculant (ABF) were performed by FTIR and NMR analysis, which represented the structure of →3) [β-D-Man iii (1 → 6) α-D-Gal ii (1 → 6)] α-D-Glc i (1 → . ABF was very well utilized for the flocculation recovery of the microalgae Nannochloropsis . ABF showed a higher flocculation rate of 99.18% at 0.5% concentration in less than 10 min on Nannochloropsis culture medium. The flocculation effect of ABF was compared with the chemical flocculants. Considering the previous literature reports and the efficiencies of the chemical flocculants, the ABF was found to be a novel and effective bioflocculant to be used in the flocculation recovery of the microalgae. In future, the polysaccharide based bioflocculants can be used for microalgal harvesting via a greener and ecofriendly technology. Graphical abstract: Image 1 Highlights: Novel polymeric bioflocculant produced from marine actinobacterium Streptomyces sp. ABF represented .→3) [β-D-Man iii (1 → 6) α-D-Gal ii (1 → 6)] α-D-Glc i (1→ repeating units. ABF showed a higher flocculation rate of 99.18% at 0.5% compare to Nannochloropsis culture medium.